2019
DOI: 10.1097/tp.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approaches to Allosensitization and Antibody-mediated Rejection

Abstract: Modification of pathogenic antibodies and their effector functions in autoimmune diseases or use of B cell/plasma cell‐directed anticancer therapies have illuminated the biologic relevance of B cells, plasma cells (PCs), and pathogenic antibodies and complement in alloimmunity. They have also rejuvenated interest in how B cells mediate multiple effector functions that include antibody production, antigen presentation to T cells, costimulation, and the production of immune stimulating and immune modulatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 107 publications
0
21
0
Order By: Relevance
“…10 As evidence supporting antagonism of the CD28 pathway to combat alloantibodies mounts, 19 it is foreseeable that more potent forms of CD28 blockade will be desired in cases of highly sensitized patients or potential costimulation blockade-based desensitization protocols. 6 Here, we demonstrate that selective CD28 blockade is better than CTLA-4-Ig at inhibiting the humoral alloresponse in a clinically relevant full allogeneic mismatch model and that this superior inhibition is mechanistically CTLA-4-dependent and Tfh cell specific.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…10 As evidence supporting antagonism of the CD28 pathway to combat alloantibodies mounts, 19 it is foreseeable that more potent forms of CD28 blockade will be desired in cases of highly sensitized patients or potential costimulation blockade-based desensitization protocols. 6 Here, we demonstrate that selective CD28 blockade is better than CTLA-4-Ig at inhibiting the humoral alloresponse in a clinically relevant full allogeneic mismatch model and that this superior inhibition is mechanistically CTLA-4-dependent and Tfh cell specific.…”
Section: Discussionmentioning
confidence: 75%
“…These donor‐specific antibodies (DSA) have been increasingly recognized to cause immunologic injury of kidney allografts and present a barrier to improving long‐term outcomes. Despite the deleterious role of DSA, large knowledge deficits exist regarding the mechanisms underlying their development and maintenance, and therapeutic strategies to control DSA‐mediated allograft dysfunction are lacking 5‐7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we discuss novel and emerging therapeutics that likely will offer significant benefits over existing therapies in prevention and treatment of AMR. [1][2][3] A review of the immune activation pathways responsible for AMR are shown in Figure 1A and Table 1.…”
Section: Antibody-med Iated Re Jec Ti On: the Prob Lemmentioning
confidence: 99%